Thermoelectric energy harvesting for wireless self powered condition monitoring nodes - Royo Perez, Sandra (Cranfield University, 2013)
Condition monitoring of machines and structures is commonly utilized in order to prevent failures before they can occur. For these reasons, data such as temperature, vibrations or displacements are collected and analysed. Sensors collect this information, which is sent to a base station to be examined. Wired sensors have been used since the appearance of condition monitoring maintenance; however, wireless sensors are becoming more popular in this area. The use of wired sensors can be very expensive, due to the cost related to the installation and maintenance of the wiring between the sensors and the base station. In wind turbines, wired sensor networks are starting to be substituted by wireless sensor networks. However, for tidal turbines, such as those developed by Delta Stream, this is still a challenge. The use of batteries to supply energy to sensors is not an optimal solution for turbines that are located in remote areas. Batteries have a limited life and their replacement is costly and complicated. Thus, alternative sources of energy have to be found. The environment found in a tidal turbine provides several sources of profitable energy, such as vibration and temperature differences which can be used to supply energy by means of energy harvesters. The aim of this project is to demonstrate the operation of self-powered short-range wireless sensor nodes for a potential use in a Delta Stream nacelle of tidal turbine. This project focuses on the wireless communication inside the nacelle (where most of the sensors are located) using a land protocol (Zigbee), and the energy harvesting using waste heat by means of thermoelectric devices. In order to prove the operation of the whole system (thermoelectric generator and sensor node), a power management circuit was also constructed and tested.
Keywords: Wireless sensors; tidal turbine; thermoelectric harvester; temperature difference; Zigbee